Panasuan language, derivational verb, affixation - Jerniati I. (SAWERIGADING, 2014)
The research aims at describing affixes that form the verbs of Panasuan language. It uses descriptive qualitative method with techniques of collecting data by elicitation, recording, and noting. Result of research shows that derivational verbs of Panasuan languages determine its part of speech when they are embedded with basic verbs, while derivations are embedded with noun and adjective. Morphophonemic process only happens on prefix affixation.